2020
DOI: 10.1111/add.15180
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of alcohol as a contributor to death in Australian national suicide statistics and its relationship to post‐mortem alcohol concentrations

Abstract: Aim To describe the assignment of International Classification of Disease (ICD)‐10 alcohol codes as underlying or contributory causes of death by the Australian Bureau of Statistics during mortality coding for suicides according to the blood alcohol concentration (BAC) detected at autopsy. Design Population‐based case‐series descriptive analysis. Setting and participants Data for all alcohol‐related (Alc+) suicide deaths (aged 15+) in Australia from 2010–2015 (n = 3132) from the National Coronial Information S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…35 Previous studies also suggested an association between alcohol drinking and suicide attempt. [36][37][38][39] The results of the present study on the relationship between suicide attempt and substance abuse and alcohol drinking can be a challenging finding that should be considered in future research in the same community.…”
Section: Discussionmentioning
confidence: 90%
“…35 Previous studies also suggested an association between alcohol drinking and suicide attempt. [36][37][38][39] The results of the present study on the relationship between suicide attempt and substance abuse and alcohol drinking can be a challenging finding that should be considered in future research in the same community.…”
Section: Discussionmentioning
confidence: 90%
“…Alternatively, assigning cause of death may be avoided entirely by reporting all‐cause mortality during a defined period, such as within 12 months of notification. This, however, runs counter to existing Australian death classification systems, and may introduce other problems such as under‐recognition of secondary conditions contributing to the risk of disease‐specific mortality 12 …”
Section: Discussionmentioning
confidence: 92%
“…This, however, runs counter to existing Australian death classification systems, and may introduce other problems such as under-recognition of secondary conditions contributing to the risk of disease-specific mortality. 12 While the differences highlighted here reflect several thematic issues, broad consensus on death classification is critical for monitoring this key outcome measure. NTAC intends to develop a national policy statement to contextualise these findings and improve within-jurisdictional and cross-jurisdictional standardisation.…”
Section: Discussionmentioning
confidence: 98%
“…69 Methods to assess the pairwise occurrence of causes were used frequently in external cause epidemiology, specifically to assess the nature of poisoning and injury related to exposure to drugs and alcohol. [85][86][87][88][89] While the nature of the coding process mandates the use of multiple causes of death for assessing injuries sustained from external causes, descriptive pairwise analysis has also been applied to infectious diseases [90][91][92][93][94] and chronic diseases. 3,[95][96][97][98][99][100][101] More complex applications such as the assessment of mortality odds ratios were applied to assess the strength of relationships between diseases on the death certificates.…”
Section: Discussionmentioning
confidence: 99%